ANALISIS “AIDA” PADA KONTEN INSTAGRAM “MADAME GIE” TERHADAP MINAT BELI KONSUMEN - Donna Carollina; Yongkie Angkawijaya; Victor Adiluhung Abednego (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2022)
This research aims to examine Madame Gie's Instagram content with consumer buying interest based on attention, interest, desire, and action (AIDA). This research uses the descriptive qualitative method. The data collection was carried out using a questionnaire distributed online to 100 followers of the Madame Gie account as the research sample. The results found the relations between Madame Gie's Instagram content with consumer buying interest based on AIDA aspects. In the attention aspects, pastel colors and celebrities' photos and videos use to attract the audience. In the interest aspects, the consistency of uploading photos and product content makes it easier for the audience to know the product. In the desire aspects, content that displays various product advantages such as product variants and testimonials encourages the audience to make a purchase or action.